NOISE AND THE DESIGN OF AN ACOUSTIC ENVIRONMENT - Párraga Velásquez, María (2005)
This study presents general concepts about noise and its effects on people. It also makes suggestions to design an appropriate and comfortable acoustic environment to workers.